2018
DOI: 10.4314/ijbcs.v12i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Azadirachta indica</i> leaf aqeous extract on the antioxidant enzymes in paracetamol-induced hepatotoxicity in Wistar rats

Abstract: Azadirachta indica, reported to be antioxidative, is hepatoprotective. This study evaluates the effect of A. indica leaf aqueous extract on antioxidant enzymes (glutathione peroxidase (GPx), superoxide dismutase (SOD) in paracetamol induced hepatotoxicity in Wister rats. Twenty four rats, in four groups, each containing six rats were used. Group A was given normal saline, group B paracetamol (800 mg/kg body weight) and groups C and D paracetamol and graded doses of the extract (400 mg and 800 mg/kg body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
4
11
0
2
Order By: Relevance
“…Most hepatic pathologies are associated with elevated levels of ALP and other enzymes that include AST and ALT. Decreased in ALP levels in this study may therefore be associated with hepatoprotective function which has been demonstrated for A. indica in previous studies (Nwobodo et al, 2018). Bilirubin, albumin, and globulin were not significantly different from control.…”
Section: Discussionsupporting
confidence: 82%
“…Most hepatic pathologies are associated with elevated levels of ALP and other enzymes that include AST and ALT. Decreased in ALP levels in this study may therefore be associated with hepatoprotective function which has been demonstrated for A. indica in previous studies (Nwobodo et al, 2018). Bilirubin, albumin, and globulin were not significantly different from control.…”
Section: Discussionsupporting
confidence: 82%
“…Histopathological findings from different resources showed that AzadirachtaIndica and Vitamin E has also a positive influence on biochemical parameters. The defensive alterations to cellular injury are reflected in the healing activity found in liver cells of animals treated with paracetamol 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Des valeurs proches de l'activité des peroxydases de Curculigo pilosa et Stylochyton hypogaeus ont été observées dans la racine de Daucus carota (Santos de Araujo et al, 2004). Quant à B. bengeri, son activité peroxydasique est proche de celle de la glutathion-peroxydase obtenu par Nwobodo et al (2018).…”
Section: Discussionunclassified